Monetary policy and stock market volatility in ASEAN5: asymmetries over bull and bear markets - Zare, Roohollah; Mohamed, Azali; Habibullah, Muzafar Shah (Elsevier, 2013)
This paper examines the asymmetric response of stock market volatility to monetary policy over bull and bear market periods in ASEAN5 countries (Malaysia, Indonesia, Singapore, the Philippines and Thailand) using the well-tested pooled mean group (PMG) technique. Bull and bear markets are identified by employing Markov-switching models and the rule- based non-parametric approach. Estimating the models using monthly data from 1991:1 to 2011:12, the results show that a contractionary monetary policy (interest rate increases) has a stronger long-run effect on stock market volatility in bear markets than bulls consistent with the prediction of finance constraints models.